The Harriet Lane handbook : a manual for pediatric house officers - Anderson, Camille C.; Kapoor, Sunaina (Philadelphia, PA : ELSEVIER, 2024)
Every three years, The Harriet Lane Handbook is carefully updated by residents, edited by chief residents, and reviewed by expert faculty at The Johns Hopkins Hospital. Easy to use, concise, and complete, this essential manual keeps you current with new guidelines, practice parameters, pharmacology, and more--Publisher's description
Part I. Pediatric acute care. Emergency and critical care management -- Traumatic injuries -- Toxicology -- Procedures -- Part II. Diagnostic and therapeutic information. Adolescent medicine -- Analgesia and procedural sedation -- Cardiology -- Dermatology -- Development, behavior, and developmental disability -- Endocrinology -- Fluids and electrolytes -- Gastroenterology -- Genetics : metabolism and dysmorphology -- Hematology -- Immunology and allergy -- Immunoprophylaxis -- Microbiology and infectious disease -- Neonatology -- Nephrology -- Neurology -- Nutrition and growth -- Oncology -- Palliative care -- Psychiatry -- Pulmonology and sleep medicine -- Radiology -- Rheumatology -- Part III. Blood chemistries and body fluids -- Biostatistics and evidence-based medicine -- Part IV. Drug dosages -- Drugs in renal failure.
Revised edition of: The Harriet Lane handbook : a manual for pediatric house officers / the Harriet Lane Service, Children's Medical and Surgical Center of the Johns Hopkins Hospital; editors, Helen Hughes, Lauren Kahl. Twenty-Second edition. [2021]
Includes bibliographical references and index.
Keywords: Pediatrics